2015
DOI: 10.1038/eye.2015.245
|View full text |Cite
|
Sign up to set email alerts
|

Surgical challenges and outcomes of rhegmatogenous retinal detachment in albinism

Abstract: Purpose To report the outcomes and surgical difficulties during rhegmatogenous retinal detachment (RRD) repair in patients with albinism. Methods Retrospective analysis of 10 eyes of 9 patients with albinism that underwent RRD repair was performed. Collected data included demographic details, preoperative examination details, surgical procedure, surgical difficulties, anatomical, and visual outcomes. Outcome measures were retinal reattachment and visual acuity at the last follow-up. Results Mean preoperative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 7 publications
0
20
1
Order By: Relevance
“…It was stated that there is less PVR in albino RD. 1 The current multiracial case series may not support that previous conclusion. The presence of PVR was noted in some of our patients: 1) late presentation of RD; 2) the need for high energy laser or cryotherapy may also trigger PVR; and 3) the need for several surgeries and the low success rate with one operation.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…It was stated that there is less PVR in albino RD. 1 The current multiracial case series may not support that previous conclusion. The presence of PVR was noted in some of our patients: 1) late presentation of RD; 2) the need for high energy laser or cryotherapy may also trigger PVR; and 3) the need for several surgeries and the low success rate with one operation.…”
Section: Discussioncontrasting
confidence: 84%
“…Retinal detachment in albinism is rarely discussed in the literature. 1 – 4 Several problems arise in such conditions: inadequate visualization of retinal breaks from loss of contrast between retina and choroid, 1 the inability for the laser to induce a good chorioretinal adhesion, and fast nystagmus that aggravates vitreous currents. Our study aims to further extend prior observations 1 – 4 and identify retinal detachment outcomes in a large original case series.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Both the cases needed cryoablation of retina to complete the treatment. Sinha et al in a series of six cases of RRD in ocular albinism have reported that after settling the detached retina, visible laser reaction could be achieved in three out of six cases using Argon green laser (532 nm) with power 200–400 mW and a duration of 150–300 ms.[5] Huang et al have suggested using Argon yellow laser with a longer duration (300–500 ms) to achieve adhesion between neurosensory retina, RPE, and choriocapillaris in a case of RRD associated with ocular albinism. [6] Laser reaction has also been documented using Krypton red laser in a case of RRD with ocular albinism.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, only one case has been reported of a patient with albinism who developed proliferative diabetic retinopathy, 2 with a few other reports describing patients with albinism who developed retinal detachments due to other causes. 3 , 4 , 5 , 6 In these previous patients, major reported challenges included control of diabetic neovascular proliferation, identification of retinal breaks, and lack of laser uptake. In this case, our challenges were similar.…”
Section: Discussionmentioning
confidence: 99%